2022
DOI: 10.1155/2022/9723632
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Inhibits Pyroptosis in Diabetic Cardiomyopathy through the Nrf2 Pathway

Abstract: The present study investigated whether quercetin promotes the nuclear translocation of nuclear factor erythroid-2-related factor 2 (Nrf2) to inhibit pyroptosis progression and ameliorate diabetic cardiomyopathy. We evaluated the protective effects of quercetin against diabetic cardiomyopathy by analyzing the expression of pyroptosis pathway proteins, myocardial cell apoptosis rate, degree of myocardial fibrosis, and serum inflammatory indices in the hearts of model rats with diabetes. We evaluated the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…These results provide strong evidence that IL-37 inhibits macrophage ferroptosis by activating the NRF2 pathway. As a classical transcription factor, a large number of studies have reported that the transfer of NRF2 to the nucleus is the key to the biological function of NRF2 ( 18 , 28 , 44 ). It was reported that lycopene ameliorates DEHP exposure-induced renal pyroptosis through enhancing NRF2 nuclear translocation ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results provide strong evidence that IL-37 inhibits macrophage ferroptosis by activating the NRF2 pathway. As a classical transcription factor, a large number of studies have reported that the transfer of NRF2 to the nucleus is the key to the biological function of NRF2 ( 18 , 28 , 44 ). It was reported that lycopene ameliorates DEHP exposure-induced renal pyroptosis through enhancing NRF2 nuclear translocation ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that Gps can improve myocardial injury and control the progression of DCM by inhibiting the activation of ROS‐induced NLRP3 inflammasome. It has been found that quercetin can reduce the levels of inflammatory cytokines in a diabetic rat model, inhibit the expression of pyroptosis proteins, increase the levels of antioxidant factors, reduce ROS accumulation, and effectively inhibit the pyroptosis process, thereby improving DCM (Z. Wei, Jing, et al, 2022). An experiment involving intervention with ginsenoside Rb1 in mice with diabetic cardiomyopathy (DCM) showed significant improvements in oxidative stress and inflammatory response in the hearts of DCM mice after ginsenoside Rb1 intervention.…”
Section: Natural Substances Treat Dcm By Targeting Different Pcdsmentioning
confidence: 99%
“…22 Additionally, ML385 (5 mg/mL) dissolved in DMSO was administered weekly by ip injection (20 mg/kg body weight) for 6 weeks. 23 Animals that served as controls were injected with the same volume of DMSO or normal saline alone. each of the other groups, with each group housed in separate cages.…”
Section: Establishment Of Rat Modelmentioning
confidence: 99%
“…The concentration of nigericin (an activator of NLRP3) used in the experiments was 10 μM, which has been confirmed in previous studies. 23…”
Section: Cell Line Model Of Doxorubicin-induced Cardiotoxicitymentioning
confidence: 99%